PENGEMBANGAN MODEL MENTORING UNTUK MENINGKATKAN KINERJA GURU PEMULA DI SMPN 2 BANYUGLUGUR - Imroatun Dilla Mufidah; Muhammad Kholil (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Novice teachers frequently encounter various challenges in carrying out their professional responsibilities, particularly in lesson planning, classroom management, learning assessment, and adaptation to the school environment. This study aimed to develop a mentoring model to enhance the performance of novice teachers at SMP Negeri 2 Banyuglugur. The study employed a Research and Development (R&D) approach involving nine participants, consisting of one principal, three senior teachers serving as mentors, and five novice teachers as mentees. Data were collected through observations, in-depth interviews, and documentation and were analyzed using data reduction, data display, and conclusion-drawing techniques. The findings revealed that novice teachers require systematic professional support in designing instructional materials, managing classrooms, conducting learning assessments, and strengthening self-confidence and professionalism. Based on the needs analysis, a cyclical mentoring model was developed comprising four stages: planning, implementation, evaluation, and follow-up. The implementation of the model demonstrated improvements in novice teachers’ engagement in instructional activities, classroom management skills, use of diverse teaching strategies, and openness to feedback and reflective practices. These findings indicate that the developed mentoring model effectively supports the professional development and sustained performance improvement of novice teachers.